Indigenous river bacteria from West Java, Indonesia with copper tolerance and malachite green decolorization potential - WAHYU IRAWATI; IMMANUELLA GRACE KRISTINA; REINHARD PINONTOAN; MARCELIA SUGATA (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Irawati W, Kristina IG, Pinontoan R, Sugata M. 2026. Indigenous river bacteria from West Java, Indonesia with copper tolerance and malachite green decolorization potential. Biodiversitas 27 (2): d270222. https://doi.org/10.13057/biodiv/d270222. River ecosystems are important reservoirs of freshwater biodiversity, but are increasingly threatened by textile-derived dyes and heavy metals. These contaminants impose chronic chemical stress, so selecting pollution-adapted indigenous bacteria represents a valuable biological resource for sustainable bioremediation. Three indigenous bacterial isolates from textile-polluted rivers in West Java, Indonesia—Lysinibacillus capsici CKJ 1000 1.1, Bacillus proteolyticus CKJ 1000 2.2, and Bacillus cereus CTR 200 1.1—were evaluated for copper (Cu) tolerance, while Cu biosorption in LB broth (2% inoculum, OD600 = 0.8, 48 h, 37°C, 150 rpm) was quantified by atomic absorption spectrophotometry. MG resistance and decolorization were examined on MG-supplemented agar (0, 10, 20, 50, and 100 ppm) and in liquid LB (10 or 20 ppm; 48 or 96 h) using UV-Vis spectrophotometry. Putative MG transformation products were further profiled using LC-HRMS. L. capsici exhibited reduced growth at ≥8 mM, whereas B. cereus and B. proteolyticus demonstrated higher tolerance, maintaining growth even at 10 mM CuSO₄. Copper biosorption was the highest in L. capsici (13.71% at 4 mM CuSO₄), followed by B. cereus (10.8%) and B. proteolyticus (9.10%). MG decolorization showed clear strain-dependent variation; at 10 ppm MG after 48 h, L. capsici achieved the highest decolorization efficiency (92.50%), followed by B. cereus (68.68%) and B. proteolyticus (47.62%). This study provides the first quantitative comparison of copper biosorption and MG decolorization under standardized conditions for these indigenous riverine isolates, coupled with LC-HRMS profiling of MG transformation products for the top-performing strain. Putative transformation products, including aniline and benzophenone derivatives, were detected; however, ecotoxicity was not assessed, and the environmental safety of the resulting metabolites cannot be concluded. These findings highlight pollution-adapted freshwater bacteria as promising biological resources for integrated metal-dye bioremediation, pending further toxicological validation.